c) - 23-(-6).(+3).
Matheus
Soluções para a tarefa
Respondido por
4
Resposta:
- 5
Explicação passo a passo:
> regra de sinais:
( + ) com ( + ) = ( + )
( - ) com ( - ) = ( + )
( + ) com ( - ) = ( - )
( - ) com ( + ) = ( - )
-------------------------
- 23 - ( - 6 ) . ( + 3 )
= - 23 - ( - 18 )
= - 5
SwiftTaylor:
Muito Bom
Respondido por
4
Resposta:
OLÁ
- ❈ o resultado da expressão é -5
RESOLUÇÃO
______
espero ter ajudado
____________________
Anexos:
![](https://pt-static.z-dn.net/files/d1b/35e14b6d9a81cbf5842a7b73a6e6f722.jpg)
Perguntas interessantes